Maintenance on naltrexone + amphetamine decreases cocaine-vs.-food choice in male rhesus monkeys. (1st December 2017) - Moerke, Megan J.; Banks, Matthew L.; Cheng, Kejun; Rice, Kenner C.; Negus, S. Stevens
Highlights: Morphine increased cocaine choice and decreased rates of reinforcement. Naltrexone alone had no effect on cocaine choice. Naltrexone enhanced the potency of amphetamine to reduce cocaine choice. Abstract: Background: Cocaine use disorder remains a significant public health issue for which there are no FDA-approved pharmacotherapies. Amphetamine maintenance reduces cocaine use in preclinical and clinical studies, but the mechanism of this effect is unknown. Previous studies indicate a role for endogenous opioid release and subsequent opioid receptor activation in some amphetamine effects; therefore, the current study examined the role of mu-opioid receptor activation in d -amphetamine treatment effects in an assay of cocaine-vs-food choice. Methods: Adult male rhesus monkeys with double-lumen intravenous catheters responded for concurrently available food pellets and cocaine injections (0–0.1 mg/kg/injection) during daily sessions. Cocaine choice and overall reinforcement rates were evaluated during 7-day treatments with saline or test drugs. Results: During saline treatment, cocaine maintained a dose-dependent increase in cocaine-vs.-food choice. The mu-opioid receptor agonist morphine (0.032–0.32 mg/kg/h) dose-dependently increased cocaine choice and decreased rates of reinforcement. A dose of the mu-selective opioid receptor antagonist naltrexone (0.0032 mg/kg/h) that completely blocked morphine effects had no effect on cocaine choice when it was administered alone, but it enhanced the effectiveness of a threshold dose of 0.032 mg/kg/h amphetamine to decrease cocaine choice without also enhancing nonselective behavioral disruption by this dose of amphetamine. Conversely, the kappa-selective opioid antagonist norbinalorphimine did not enhance amphetamine effects on cocaine choice. Conclusions: These results suggest that amphetamine maintenance produces mu opioid-receptor mediated effects that oppose its anti-cocaine effects. Co-administration of naltrexone may selectively enhance amphetamine potency to decrease cocaine choice without increasing amphetamine potency to produce general behavioral disruption.